Evaluating Differentiated Learning in Merdeka Curriculum to Strengthen Pancasila Students’ Profile - Makrufi Anisa Dwi; Syahrir Muhammad (SHS Web of Conferences)
This study examined the implementation of differentiated learning in the Merdeka Curriculum and its impact on strengthening the Pancasila learner profile in students in Yogyakarta. Using the countenance stake evaluation model with a qualitative approach, this study involved 17 teachers from five elementary schools. The results showed teachers’ positive perceptions of differentiated learning, with 82.4% of teachers finding the curriculum flexible. Strategies implemented by teachers included early assessment, project-based learning, and continuous evaluation. Learners showed positive responses, with 58.8% strongly reflecting Pancasila values in their daily lives. Differentiated learning is proven to improve learning motivation, material understanding, and internalization of Pancasila values. This study concludes that differentiated learning in the Merdeka Curriculum has the potential to create a young generation that is adaptive, creative, and has a strong character according to the values of Pancasila. Further research can optimize the integration of this approach into learning practices and evaluate its overall impact.